Pengaruh Promosi dan Harga Terhadap Peningkatan Jumlah Nasabah Produk Akad Murabahah Di BPRS Artha Madani Cabang Cikampek - Meida Fitriani 04 (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2020)
Abstract— This research was conducted at the BPRS Artha Madani branch Cikampek. The problem that occurs in the field is a decrease in the number of customers that occurred in 2018. Total all sample of 84 peoples. Researchers use the theory of Philip Kotler to be a reference in developing the theoretical foundation that studies the concepts of marketing, promotion and price. Primary data collection through interviews with branch heads. Distribution of questionnaires, with respondents determined using the Slovin formula. The method used in this study is a quantitative method, a method that uses numbers in each result and is tested using the SPSS application. Data analysis techniques used in this study are data validity, data reliability, for the classical assumption test using the normality test, multicolleration test, and heteroscedastic test. Whereas the hypothesis test uses the determination test, partial test (t test), multiple linear regression, and simultaneous test (f test). The results showed that the promotion variable did not significantly influence the percentage of 24.20%. Meanwhile, the price variable significantly affected the percentage of 63.65% on the increase in the number of customers. Based on the simultaneous test (f test) that has been done that the promotion and price variables together affect the increase in the number of customers. The results of the determination test or R2 that have been done get the results that, promotion and price affect the increase in the number of customers by 51.9% and the remaining 48.1% is influenced by other variables outside the study. Keywords—: Promotion And Price, Increase In Number, Murabahah Contract.